COVID-19 outcomes in a large pediatric hematology-oncology center in Houston, Texas. (17th November 2021) - Kamdar, Kala Y.; Kim, Taylor O.; Doherty, Erin E.; Pfeiffer, Thomas M.; Qasim, Shawki L.; Suell, Mary Nell; Yates, Amber M.; Blaney, Susan M.
Abstract: An understanding of the behavior of SARS-CoV-2 in pediatric hematology-oncology patients is essential to the optimal management of these patients during the COVID-19 pandemic. This study describes the characteristics and outcomes of COVID-19 disease in children with cancer or hematologic disorders treated at a large children's hospital. A retrospective cohort study was conducted at Texas Children's Cancer and Hematology Center from January 1, 2020 to September 30, 2020. All patients with a primary hematology-oncology diagnosis and SARS-CoV-2 positivity by reverse transcription polymerase chain reaction were identified. Clinical and laboratory data were obtained from the medical record. Descriptive analyses were performed to evaluate COVID-19-related outcomes and risk factors for severe disease in this population. We identified 109 patients with COVID-19 disease, including 52 hematology, 51 oncology, and 6 HSCT patients; median age was 10.3 years (IQR 4.4–15.9), and 58.7% were male. Seventy-four percent of the patients were managed in the outpatient setting. Patients with sickle cell disease were more likely to require hospitalization. ICU care was needed in 8% (n = 9) of the entire cohort, and mechanical ventilation was required in 6.4% (6 oncology patients, 1 hematology patient). COVID-19 contributed to the deaths of two cancer patients. No deaths occurred in hematology or HSCT patients. In conclusion, the risk of severe COVID-19 complications is slightly higher in pediatric hematology-oncology patients than in the general pediatric population but lower than initially feared. For most asymptomatic patients, primary disease management may continue as planned, but treatment decisions must be individualized.